Arrimer les compétences individuelles des personnes âgées et l’accessibilité des territoires de banlieue pour une mobilité durable - Paula Negron-Poblete (VertigO, 2012)
Mobility is often addressed as a simple matter of modal choice, focusing exclusively on travel patterns, transport modes and their impacts on the environment. However, in an approach to sustainable mobility, it is equally important to assess the capacity of territories to provide good accessibility to everyone. This forces us to concern ourselves not only about places to which people wish to access and territories’ physical attributes, but also about the individual skills that people can apply to their own mobility, skills that evolve with a person´s life cycle. Thus, unrealized trips may actually reflect a mismatch between individual skills and territories’ physical attributes where personal mobility projects take place. Given that in the years to come the first-ring suburbs of our metropolis will be greatly affected by aging, we can already predict a decline in individual skills invested in personal mobility projects, including automobile use. What strategies seniors will be able to put forth to maintain their mobility projects if they’re no longer able to drive ? Do these aging territories will meet new capacity and mobility needs of their inhabitants ? In putting forward the link between mobility, accessibility and aging, this article aims to contribute to the debate surrounding the ability of suburban areas to enable sustainable mobility that takes into account the mobility skills of their aging populations.